2010
DOI: 10.1172/jci40908
|View full text |Cite
|
Sign up to set email alerts
|

FAVL elevation in human tumors disrupts Fanconi anemia pathway signaling and promotes genomic instability and tumor growth

Abstract: Fanconi anemia (FA) is a rare human genetic disease caused by mutations in any one of 13 known genes that encode proteins functioning in one common signaling pathway, the FA pathway, or in unknown genes. One characteristic of FA is an extremely high incidence of cancer, indicating the importance of the FA pathway in tumor suppression. However, the role of this pathway in the development and progression of human cancers in individuals who do not have FA has not been clearly determined. Here, we report that elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 41 publications
(62 reference statements)
7
61
0
Order By: Relevance
“…Indeed, splice variants seem to act as regulators of the FA pathway, as observed in the well-characterized FAVL variant. In that case, FAVL has been demonstrated to promote FANCL degradation42,77 . The expression of the splice isoform was increased in the presence of sequence variation rs77950394 and rs182189246, while rs13214239 reduces its expression.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, splice variants seem to act as regulators of the FA pathway, as observed in the well-characterized FAVL variant. In that case, FAVL has been demonstrated to promote FANCL degradation42,77 . The expression of the splice isoform was increased in the presence of sequence variation rs77950394 and rs182189246, while rs13214239 reduces its expression.…”
mentioning
confidence: 99%
“…Only a few FANCE-deficient patients were identified to date but most of them display several major abnormalities, thus demonstrating the importance of the integrity of the FANCE protein39,40 . Alternatively splice isoforms were previously analyzed and characterized for other FA genes namely FANCA, FANCC or FANCL35,[41][42][43] . This study represents the first characterization of a FANCE splice isoform lacking the exon 4 (designated FANCE∆4) and annotated in the NCBI database as XM_005248886.1.Co-immunoprecipitation and yeast-2-hybrid studies have already demonstrated the direct interaction of the FANCE protein with FANCC and FANCD2, thus suggesting that binding of FANCE∆4 with these partners could be altered32,44 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed before, defects of the FA/BRCA pathway in cancer cells have also been related to the expression of FA variant proteins, such as the FAVL variant [41]. As is the case in conventional FA cells, cell lines expressing high levels of FAVL were hypersensitive to MMC, an observation with evident implications in the development of optimised cancer therapies with DNA ICL agents.…”
Section: Signifi Cance Of the Fanconi Anaemia Pathway In The Cell Resmentioning
confidence: 90%
“…Strikingly, in their study, Zhang et al observed that FAVL was expressed in 50% of tested carcinoma cell lines and primary carcinomas, and that expression of FAVL mediated a decrease in FANCL expression. Moreover, FAVL provided cancer cells with a growth advantage, caused chromosomal instability and promoted tumour development in a xenograft mouse model [41].…”
Section: The Fanconi Anaemia Pathway and Sporadic Cancermentioning
confidence: 99%